Ofiary z ludzi w obrzędowości rzymskiej – mamuralia, sacra argeorum, saturnalia, compitalia - Kaczor, Idaliana (Collectanea Philologica, 2015)
Apotropaic behaviours in the Roman system of beliefs required the use of various forms of offerings in order to achieve the expected sacral goal. We may assume, that a full effectiveness of such actions was asserted only by human sacrifice. Along with the development of religious practices the Romans substituted human sacrifice however, in times of serious danger for the Roman community, they would reach for the early sacral experiences. In the system of Roman beliefs extremely important appeared to be the rituals at the turn of the year, which represented the periodic change of the tempus sacrum. Many of the rituals of the turn of the year played the role of lustrative rites, which were extended into practices of liberating the community from sacral miasma and received those rites which represented the destruction of cosmic order and its recovery to the state of primordial chaos. These types of ceremonies might have required a human sacrifice.